Gambang: The Gamelan Wooden Xylophone - Sinin, Hamdan; Md Rezaur, Rahman; Ahmad Faudzi, Musib; Saiful Hairi, Othman (BioResources, 2022)
This work investigated the ironwood used to construct a gambang, which is a traditional musical instrument. A gambang is constructed from a wooden bar with a similar thickness and width but a different length. The sound and established frequencies were compared with the equal tempered scale. The peak differed from the intended pitch and the partials were not always harmonic. This gambang only classified 4 octaves. The audio classification of the gambang was based on signal processing using a Picoscope oscilloscope. This article explains how wood is transformed into musical instruments. The findings revealed that the sound aspect and sound value of the wood keyboard instruments differed from the desired bitch. The third octave notes created C5, E5, E5, G5, and A5 instead of C5, D5, E5, G5, and A5, while the fourth octave pitch produced C6, D6, E6, G6, and A6# instead of C6, D6, E6, G6, and A6. Only the third and fourth octaves exhibited nearly flawless tuning for the gambang.